Male Income, Female Income, and Household Income Inequality in Israel: A Decomposition Analysis - Kimhi, Ayal (Journal of Income Distribution®, 2009)
Differentiating between the sensitivity of income inequality to male income and female income and decomposing inequality by income determinants, we find that total income inequality is less sensitive to female income variability or the level of female income, than to male income variability or the level of male income. Uniform increases in education reduce income inequality, with increases in female education having a larger effect than increases in male education. An increase in the population fraction of ethnic minorities has a positive effect on inequality, but this operates mostly through female income. All this suggests that female income is the most adequate target for inequality-reducing policy, and that within-household gender equality is good for reducing income inequality among households.